Integrated biodiesel and biogas production from Chlamydomonas reinhardtii - Manasa V Anand; Madhu H N (International Journal of Pharma and Bio Sciences, 2020)
In this study, we focus on the production of energy efficient Biodiesel and Biomass, whose principle is to extract the maximum amount of energy from biomass, the biodiesel production i.e. the lipid extraction from the biomass through the trans-esterification process and the residue is then subjected for the anaerobic process for biogas (methane) production and the leftover residue can be used for various other purposes. From this study we observed that cultivation of microalgae in open pond system using fertilizer as nutrients will reduce the most of biomass production since construction of and use of open ponds is cheaper than using photobioreactors thereby reducing the fixed capital investment. Using fertilizers as nutrient source will decrease the working capital , thus reduction in overall process but major problems like salt precipitation, evaporation and change in pH due to external environment were observed in open pond; these can be overcome by taking extra care and optimization. Gas chromatography-Mass spectroscopy (GC-MS) analysis of crude biodiesel sample confirmed the presence of fatty acid methyl ester (biodiesel). The green circle in GC-MS analysis ndicates presence of decanoic acid methyl ester. The maximum amount of biogas produced was 10 cm3 in 27 days. The maximum amount of biogas produced from the algal biomass was 12 cm3 for 18 – 27 days. The Gross calorific value was found to be 333 kcal/kg. The percentage of methane present was found to be 2.5% and the percentage of carbon dioxide present was found to be 2.59%.From the energy balance, the calorific value of the biogas produced from the residue after lipid extraction was found to be 0.81 kcal. From the feasibility study conducted, it was found that the cost of new media’s formulated using fertilizers is approximately ten times less than High Salt Media thereby reducing the overall cost which improves the economics of biodiesel production.